Histomorphometric Assessment of Surgically Made Alveolar Bone Defects Healing in Response to Aloe Vera Gel: An Experimental Study on Rabbits - Asmaa A Hasa; Omer W Majid (University of Mosul, College of Dentistry, 2023)
Aims: The aim of the current study is to evaluate the effect of Aloe Vera gel on the healing process of surgically made maxillary alveolar bone defects and new bone tissue formation in rabbits. Materials and Methods: Twenty albino rabbits were randomly chosen to conduct the study, all selected rabbits were inhabited under the same circumstances involving ventilation, temperature, and diet. Each rabbit received the anesthetic solution separately and underwent a surgical procedure in both sides of the maxillary alveolar bone which involved a longitudinal oral mucosal incision followed by circular bone defect creation and further placement of Aloe Vera gel and a tiny gel foam piece in the left side of the animal's jaw bone, while right side bone hole was left empty for control. According to euthanization date, rabbits were divided into five groups and euthanized at the 3rd, 7th, 14th,28th, and 42 days post-surgery, the histomorphometric assessment included evaluation of the amount of granulation tissue formed and calculation of the surface area of newly formed bone tissue in relation to the microscopical field using special image analysis software. Results: Histomorphometric analysis results revealed a statistically significant difference in the amount of granulation tissue and new bone tissue surface area between control and Aloe Vera groups at all-time intervals of the study favoring Aloe Vera groups. Conclusions: Aloe Vera gel has a beneficial effect on bone healing process with its enhancement effect on new bone tissue formation.